The antagonistic activity of the synbiotic containing Lactobacillus acidophilus and pineapple residue FOS against pathogenic bacteria - Ibrahem,A. A. (2024)
Abstract Fructooligosaccharide is used widely in many foods and pharmaceutical industries and produced by using different ways such as extracting it from plants or producing it by using plants and microorganisms’ enzymes. In a previous study, we extracted Fructosyltransferase (Ftase) enzyme from pineapple residue and produced FOS. In this study, we measured the antagonistic activity of two synbiotics, the first synbiotic containing Lactobacillus acidophilus and the produced FOS, the second synbiotic containing Lactobacillus acidophilus and standard FOS, against pathogenic bacteria (P. aeruginosa, E. coli, S. aureus and B cereus). The results showed that the antagonistic activity of both synbiotic types was very close, as there were no significant differences between them except in the antagonistic activity against S. aureus, there was a significant difference between the synbiotic containing the standard FOS, which was the highest in its antagonistic activity compared to the synbiotic containing the produced FOS in this study. The activity of the fructooligosaccharide (FOS) extracted from pineapple residue was evident in enhancing the activity of the probiotic bacteria (L. acidophilus), which had a major role in the production of acids and compounds that inhibited the pathogenic bacteria. The diameters of inhibition areas in the current study ranged between 19.33-28 mm, and E. coli was more susceptible to inhibition, followed by S. aureus, P. aeruginosa, and B. cereus, respectively.